Separating galaxies from the cluster dark matter halo in Abell 611. Issue 4 (23rd November 2016) - Monna, A.; Seitz, S.; Geller, M. J.; Zitrin, A.; Mercurio, A.; Suyu, S. H.; Postman, M.; Fabricant, D. G.; Hwang, H. S.; Koekemoer, A.
Abstract: We investigate the mass content of galaxies in the core of the galaxy cluster Abell 611. We perform a strong lensing analysis of the cluster core and use velocity dispersion measurements for individual cluster members as additional constraints. Despite the small number of multiply-imaged systems and cluster members with central velocity dispersions available in the core of A611, the addition of velocity dispersion measurements leads to tighter constraints on the mass associated with the galaxy component, and as a result, on the mass associated with the dark matter halo. Without the spectroscopic velocity dispersions, we would overestimate the mass of the galaxy component by a factor of ∼1.5, or, equivalently, we would underestimate the mass of the cluster dark halo by ∼5 per cent. We perform an additional lensing analysis using surface brightness (SB) reconstruction of the tangential giant arc. This approach improves the constraints on the mass parameters of the five galaxies close to the arc by a factor up to ∼10. The resulting parameters are in good agreement with the σ-rtr scaling relation derived in the pointlike analysis. The galaxy velocity dispersions resulting from the SB analysis are consistent at the 1σ confidence level with the spectroscopic measurements. In contrast, the truncation radii for 2–3 galaxies depart significantly from the galaxy scaling relation and suggest differences in the stripping history from galaxy to galaxy.